Ovarian and Hormonal Responses to Follicular Phase Administration of Investigational Metastin/Kisspeptin Analog, TAK‐683, in Goats. Issue 2 (1st February 2014) - Goto, Y; Endo, N; Nagai, K; Ohkura, S; Wakabayashi, Y; Tanaka, A; Matsui, H; Kusaka, M; Okamura, H; Tanaka, T
Contents This study evaluated the effects of follicular phase administration of TAK‐683, an investigational metastin/kisspeptin analog, on follicular growth, ovulation, luteal function and reproductive hormones in goats. After confirmation of ovulation by transrectal ultrasonography (Day 0), PGF2α (2 mg/head of dinoprost) was administered intramuscularly on Day 10 to induce luteal regression. At 12 h after PGF2α administration, intravenous administration of vehicle or 35 nmol (50 μg)/head of TAK‐683 was performed in control (n = 4) and treatment (n = 4) groups, respectively. Blood samples were collected at 6‐h intervals for 96 h and then daily until the detection of subsequent ovulation (second ovulation). After the second ovulation, ultrasound examinations and blood sampling were performed every other day or daily until the subsequent ovulation (third ovulation). Mean concentrations of LH and FSH in the treatment group were significantly higher 6 h after TAK‐683 treatment than those in the control group (12.0 ± 10.7 vs 1.0 ± 0.7 ng/ml for LH, 47.5 ± 28.2 vs 15.1 ± 3.4 ng/ml for FSH, p < 0.05), whereas mean concentrations of oestradiol in the treatment group decreased immediately after treatment (p < 0.05) as compared with the control group. Ovulation tended to be delayed (n = 2) or occurred early (n = 1) in the treatment group as compared with the control group. For the second ovulation, ovulatory follicles in the treatment group were significantly smaller in maximal diameter than in the control group (3.8 ± 0.5 vs 5.4 ± 0.2 mm, p < 0.05, n = 3). Administration of TAK‐683 in the follicular phase stimulates gonadotropin secretion and may have resulted in ovulation of premature follicles in goats.